РАЗРАБОТКА СИСТЕМЫ ОЦЕНКИ КАЧЕСТВА САЙТОВ БИБЛИОТЕК (Библиосфера, 2010)
The problem of providing high quality of culture institutions sites is considered. The system to assess the quality of library sites including the criteria and the assessing procedure is developed. Software and resources of a library were used as the bases to determine the main aspects of forming the system to assess the quality of a site. The author describes methods to collect data, as well as the process and forms suitable to determine the quality of sites.